Hukuman bagi Pelaku Judi Online : Menurut Ayat (1) Pasal 303 KUHP dan Hadits Hr. Al-Bukhari, No. 4860 Serta Muslim No. 1647 - Zaura Zahira Soffa; Tajul Arifin (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The phenomenon of online gambling has become a serious concern in Indonesia, as it provides very easy access for all groups, including teenagers and underage children, to engage in gambling practices. This study aims to examine and analyze the punishment for online gambling offenders from two perspectives: Indonesian positive law and Islamic law. Under national law, Article 303 of the Indonesian Criminal Code (KUHP) regulates criminal sanctions for gambling in any form, including digital formats. Meanwhile, Islamic law strictly prohibits all forms of gambling due to elements of speculation (gharar), one-sided loss, and its contradiction with moral values. This study uses a qualitative approach through literature review by analyzing legal sources such as the Criminal Code, legislation, hadiths, as well as fiqh and tafsir literature. The results show that both Islamic law and national law share common ground in prohibiting gambling and imposing sanctions, although they differ in their methods of implementation. Firm law enforcement and preventive measures are necessary to protect society, especially the younger generation, from the harmful impacts of online gambling.